The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12879-015-0784-4
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes, seasonal trends, and antibiotic resistance of non-typhoidal Salmonella from human patients in Guangdong Province, China, 2009–2012

Abstract: BackgroundNon-typhoidal Salmonella is a common cause of infectious diarrhea in humans. Antimicrobial-resistant Salmonella has become a global concern.MethodsUsing laboratory-based surveillance system for Salmonella from September 2009 to December 2012 in Guangdong Province of China. The clinical information and samples of diarrhea patients were collected, according to the surveillance case definition. The lab tests were followed by standardized protocols, including sample isolation, isolates confirmation, sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
68
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 34 publications
26
68
1
Order By: Relevance
“…Special difficult conditions could be found with old people and children [41,42]. Complications may occur in the elderly and immunodeficient patients with hip and knee prosthesis and poor hygiene [43].…”
Section: B Salmonella Typhimurium Atcc 14028mentioning
confidence: 99%
“…Special difficult conditions could be found with old people and children [41,42]. Complications may occur in the elderly and immunodeficient patients with hip and knee prosthesis and poor hygiene [43].…”
Section: B Salmonella Typhimurium Atcc 14028mentioning
confidence: 99%
“…In China, approximately 75% (30 million) of foodborne diseases every year are attributed to this bacterium (5). Specifically, children younger than 5 years were the group most at risk of infection by Salmonella, as noted in data obtained from several cities in China (2,6,7).…”
mentioning
confidence: 95%
“…almonellosis, caused by Salmonella enterica, is a global foodborne disease of humans and livestock worldwide (1,2). A total of 91,034 cases of human laboratory-confirmed Salmonella infections and 61 fatal cases were reported in 2012 in 27 European countries (3).…”
mentioning
confidence: 99%
“…Most of the available antibiotics, including ␤-lactams, are becoming less effective and in some cases resistance rates exceed 98% (Akinkunmi et al 2014). For example, Escherichia coli O104:H4 was found to be resistant to at least 14 different antibiotics (Verstraete et al 2013), and about 90% of Salmonella isolates were found to be resistant to one or more antibiotics tested (Dias de Oliveira et al 2005;Wang et al 2014;Liang et al 2015). Some Salmonella isolates from poultry were found to be resistant to 14 different antibiotics (Adesiji et al 2014;Zhang et al 2014).…”
Section: The Rise Of Antibiotic Resistance and Phage Revitalizationmentioning
confidence: 99%